Genetic Mutations and Polymorphisms Related to Severity, Mortality, and Antibody-Dependent Enhancement of Dengue Virus (DENV) Infection: A Literature Review - Purnamasidhi, Cokorda Agung Wahyu; Junior, Darren; Satya Diksha, I Gusti Ngurah Ariestha; Hiranandini Prawista, I Gusti Ayu Maha; Guptha, I Dewa Gede Agung Siwa; Pratyaksa, I Gusti Ngurah Dinda; Indratmo, Novea; Suteja, Richard Christian; Harkitasari, Saktivi (Institute of Topical Disease Universitas Airlangga, 2025)
The dengue virus (DENV) is a blood-borne Flavivirus transmitted through vectors and ranks as the fastest-spreading tropical disease globally. Dengue infection could exhibit mild to severe symptoms depending on various factors. Antibody-dependent enhancement (ADE) is a cross-reactive phenomenon between different DENV strains that clinicians should be aware of, as it leads to a higher incidence of dengue with warning signs and severe dengue. On the molecular level, many genes contribute to the severity and pathophysiology of ADE. Mutations and polymorphisms in these genes could alter the course of dengue infection. This article aims to comprehensively review studies that measure the impact of dengue-related genetic mutations and polymorphisms on the severity, mortality, and ADE of DENV infection. We performed a literature review to identify relevant articles on PubMed, Science Direct, Europe PMC, and Google Scholar. The review examines polymorphisms across multiple gene families: Fcγ receptors, cytokines (TNF-α, TGF-β1, IL-10), immune regulatory genes (MICB, PLCE1, RIPK2), antigen-presenting machinery (DC-SIGN, TAP), and host defense mechanisms (VDR, CTLA-4, MBL, HPA). These genetic variations have population-specific effects and may confer both protection in some populations and increased susceptibility to severe outcomes of dengue in others. The effects of these polymorphisms are context-dependent and differ according to the phase of infection, ethnicity, and gene-gene interactions. Overall, it could be concluded that aside from external factors, polymorphisms on human genes regulating mechanisms and components related to dengue infection have been extensively discussed to play a role in the overall clinical outcome.